Keuntungan dan Kelayakan Usahatani Jagung Hibrida dengan Penerapan Rekomendasi Teknologi Sistem Informasi Tanam Terpadu - Yahumri; Alfayanti; Taufik Hidayat; Darkam (AgriHumanis: Journal of Agriculture and Human Resource Development Studies, 2020)
Integrated Planting Calendar Information System (SI KATAM Integrated) is one of the technological innovations produced by the Agency for Agricultural Research and Development. Application of technology to hybrid corn plants is one way to increase productivity. The technological feasibility of all requirements of technology to be adopted by farmers. This study aims to: 1) calculate the benefits of hybrid corn farming with application of technological recommendations on the Integrated KATAM SI KM 2017 and, 2) analyze the feasibility of hybrid corn farming using technology on the SI Integrated KATAM MK 2017. The research was conducted in July-August 2017 in 11 lands cooperative farmers covering of ​​4 hectare areas in Kelurahan Kemumu, Arma Jaya District, North Bengkulu Regency. The data used to achieve the goal is primary data consisting of farm data collected in agricultural records storage. The technology applied implements Integrated KATAM SI using Bima 19 URI and Bima 20 URI varieties. Farm profit is calculated using profit analysis while farm feasibility is assessed by the R/C ratio and B/C ratio. The results showed that the farming of Bima 19 URI varieties gave a higher profit compared to Bima 20 URI with the full value of Rp. 13,312,862/MT/ha and Rp. 8,560,862 /MT/ha. Using hybrid corn with the recommended application on SI KATAM Integrated MK 2017, the economic ratio of R/C ratio >1 and farming economy is feasible to be developed with a B/C ratio of >0.